Mortal kombat legends. Snow blind [videorecording (Blu-Ray)] - Adams, Jeremy (Screenwriter) (SDS : Warner, 2022)
In a post-apocalyptic wasteland, Kuai Liang (Sub-Zero) lives a peaceful life, growing crops, and staying out of trouble. But when King Kano and the Black Dragons move in, Kuai Liang must once again become the feared Sub-Zero, to save the young warrior Kenshi and the last free outpost in Earthrealm.